Epidemiology of achondroplasia: a population-based study in Europe - Coi, A; Santoro, M; Garne, E; Pierini, A; Addor, M; Alessandri, J; Bergman, J; Bianchi, F; Boban, L; Braz, P; Cavero-Carbonell, C; Gatt, M; et al. (Wiley, 2019)
Achondroplasia is a rare genetic disorder resulting in short-limb skeletal dysplasia. We present the largest European population-based epidemiological study to date using data provided by the European Surveillance of Congenital Anomalies (EUROCAT) network. All cases of achondroplasia notified to twenty-eight EUROCAT registries (1991-2015) were included in the study. Prevalence, birth outcomes, prenatal diagnosis, associated anomalies, and the impact of paternal and maternal age on de novo achondroplasia were presented. The study population consisted of 434 achondroplasia cases with a prevalence of 3.72 per 100,000 births (95%CIs: 3.14–4.39). There were 350 live births, 82 terminations of pregnancy after prenatal diagnosis, and two fetal deaths. The prenatal detection rate was significantly higher in recent years (71% in 2011-2015 vs. 36% in 1991-1995). Major associated congenital anomalies were present in 10% of cases. About 20% of cases were familial. After adjusting for maternal age, fathers >34 years had a significantly higher risk of having infants with de novo achondroplasia than younger fathers. Prevalence was stable over time, but regional differences were observed. All pregnancy outcomes were included in the prevalence estimate with 80.6% being live born. The study confirmed the increased risk for older fathers of having infants with de novo achondroplasia.